2021
DOI: 10.3389/fmicb.2021.711545
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Growth Inhibition of Phytophthora spp. Caused by the Rare Sugar Tagatose Is Associated With Species-Specific Metabolic and Transcriptional Changes

Abstract: Tagatose is a rare sugar with no negative impacts on human health and selective inhibitory effects on plant-associated microorganisms. Tagatose inhibited mycelial growth and negatively affected mitochondrial processes in Phytophthora infestans, but not in Phytophthora cinnamomi. The aim of this study was to elucidate metabolic changes and transcriptional reprogramming activated by P. infestans and P. cinnamomi in response to tagatose, in order to clarify the differential inhibitory mechanisms of tagatose and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 70 publications
(108 reference statements)
0
26
0
Order By: Relevance
“…In recent years, some rare monosaccharides and their derivatives have shown potential functional and ecological properties in controlling plant pathogens [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Their availability has been achieved through the implementation of new enzymatic and microbial processes, making their use effective in food and agricultural sectors [ 25 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, some rare monosaccharides and their derivatives have shown potential functional and ecological properties in controlling plant pathogens [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Their availability has been achieved through the implementation of new enzymatic and microbial processes, making their use effective in food and agricultural sectors [ 25 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…D-tagatose, as a ketohexose, is among rare sugars found at low concentrations in many foods and generally recognized as safe by the Food and Drug Administration [ 30 ]. D-tagatose was shown to inhibit the growth of various plant pathogens, such as Phytophthora infestans causing late blight [ 24 ], Oidium violae causing powdery mildew in tomato [ 33 ], Plasmopara viticola (downy mildew) and Erysiphe necator (powdery mildew) in grapevine [ 32 , 33 ] and Hyaloperonospora parasitica (downy mildew) in Chinese cabbage [ 31 ]. It has been reported that D-tagatose acted directly on the pathogen by inhibiting essential enzymes leading to impairment of the whole metabolism [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In support of those findings, previous reports have noted that D-tagatose caused species-specific growth inhibition of Phytophthora spp. and decreased amino acid content in Phytophthora infestans (Chahed et al, 2020;Chahed et al, 2021). In S. oralis, the polar amino acid transporter gene (SOR_1115) was up-regulated, whereas SMU_1179c and SGO_1037, orthologous genes of SOR_1115, were down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…The alterations of mitochondrial processes found in P . infestans incubated with d ‐tagatose (Chahed et al, 2020) are associated with sugar metabolism inhibition (Chahed et al, 2021; Corneo et al, 2021b; Mochizuki et al, 2020). In particular, H .…”
Section: D‐tagatose Has Various Mechanisms Of Action Against Phytopat...mentioning
confidence: 99%
“…aureus , Pseudomonas aeruginosa , and Yersinia enterocolitica (Bautista et al, 2000), indicating antinutritional properties on specific microbial taxa. Likewise, d ‐tagatose inhibits the growth of some phytopathogens and it has been proposed as a promising plant protection product (Chahed et al, 2020, 2021; Corneo et al, 2021b; Mijailovic et al, 2021; Mochizuki et al, 2020; Perazzolli et al, 2020). The aim of this review is to summarize the current knowledge on the modes of action of d ‐tagatose against phytopathogenic oomycetes and to propose further functional studies that will support the use of this rare sugar for sustainable crop protection.…”
Section: Introductionmentioning
confidence: 99%